Business Process Evaluation and Improvement Using the Quality Evaluation Framework Approach Restaurant Management During a Pandemic (Journal of Advances in Information Systems and Technology, 2021)
Business is an activity that aims to get added value in materials or services. Currently, business is an activity carried out by various groups, and one example is the business carried out by a restaurant in one of the cities of Bandung. Several activities were less than optimal in carrying out its business processes, resulting in various complaints. This activity occurred when the Basil restaurant changed its business process, initially offline to online, due to the covid-19 pandemic. Therefore, it is necessary to evaluate using the Quality Evaluation Framework (QEF) method to find the gaps that occur. The first step is to identify the primary business processes in the workshop, then model the business processes using the Business Process Model and Notation (BPMN). Then determine the quality factor and the company's target and calculate according to the equations in the QEF method. Then identify the quality factors that are not following the company's mark. After finding a gap in the evaluation process, the next step is to carry out a Root Cause Analysis, and the goal is to find out the causes and root causes of the gap. The results of this study are the reasons for the causes of problems that occur in the evaluated business processes.